The Impact of Diabetes Self-Care, Healthy Lifestyle, Social Support, and Demographic Variables on Outcomes HbA1c in Patients With Type 2 Diabetes - Wan-Ju Chen; Li-Ying Lin (Clinical Medicine Insights: Endocrinology and Diabetes)
Background: Controlling HbA1c can help reduce the symptoms and complications of diabetes. However, only about 25% of adults with diabetes achieve this diabetes care goal. It can be seen that diabetes requires more research investment and breakthroughs, as well as a more complete discussion of related factors that affect diabetes control, in order to better control the disease. This study explored the effects of diabetes self-care behavior, healthy lifestyle, diabetes symptoms, social support, demographic variables, and physical examination values on HbA1c levels in individuals with type 2 diabetes. Methods: This study used a cross-sectional design and recruited 305 subjects with type 2 diabetes at a medical center. Personal data were collected using a structured questionnaire and same-day outpatient medical records. Results: Multiple linear regression analysis identified significant predictors of HbA1c levels. These include insulin treatment ( P  < .001), age ( P  < .001), gender ( P  < .001), diabetes duration ( P  = .003), proteinuria ( P  < .001), diabetes self-care behaviors ( P  = .021), physical activity (running; P  = .018), and spousal involvement in care ( P  = .031). Female gender, insulin treatment, longer diabetes duration, spousal involvement in care, and the presence of proteinuria were positively associated with higher HbA1c levels. In contrast, higher age, better diabetes self-care behaviors, and regular physical activity (running) were associated with lower HbA1c levels. These findings underscore the importance of considering both demographic factors and lifestyle behaviors in the management of HbA1c levels. Conclusions: For reasons that hinder subjects from controlling HbA1c levels, individual self-management intervention programs should be provided to improve the effectiveness of subjects in controlling HbA1c levels. The care giver should be included in the educational program of diabetes management. Running exercise contributes to the control of HbA1c levels.